2008
DOI: 10.1007/s00540-008-0650-2
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-oriented perioperative management of patients with bronchial asthma and chronic obstructive pulmonary disease

Abstract: Increased airway hyperresponsiveness is a major concern in the perioperative management of patients with bronchial asthma and chronic obstructive pulmonary disease. Guidelines using evidence-based medicine are continually being updated and published regarding the diagnosis, treatment, and prevention of these respiratory disorders. Perioperative management in these patients involves: (1) adequate control of airway hyperresponsiveness, including detection of purulent sputum and infection before surgery; (2) evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 165 publications
0
24
0
Order By: Relevance
“…In addition to acetylcholine, parasympathetic efferent nerve also releases vasoactive intestinal peptide and nitric oxide, which can inhibit bronchoconstriction. 29 We still do not know the role of these substances on the partial inhibition of the first peak of R L in the vagotomy study. Although our study was focused on the vagal nerve control of lung resistance, there is evidence that desflurane can activate sympathetic nerves, 30 resulting in the inhibition of airway smooth muscle contraction.…”
Section: Main Findingsmentioning
confidence: 99%
“…In addition to acetylcholine, parasympathetic efferent nerve also releases vasoactive intestinal peptide and nitric oxide, which can inhibit bronchoconstriction. 29 We still do not know the role of these substances on the partial inhibition of the first peak of R L in the vagotomy study. Although our study was focused on the vagal nerve control of lung resistance, there is evidence that desflurane can activate sympathetic nerves, 30 resulting in the inhibition of airway smooth muscle contraction.…”
Section: Main Findingsmentioning
confidence: 99%
“…According to a Japanese review of guideline-oriented management, this includes control of airway hyperresponsiveness and infection, and the aggressive use of anticholinergics in COPD and beta-2 adrenergic stimulants in asthma, as well as steroids, to limit acute exacerbations. This review also found that preoperative control with leukotriene antagonists can reduce the incidence of PCC [16]. …”
Section: Preoperative Lung Protective Strategiesmentioning
confidence: 99%
“…2 In contrast, lung physiology abnormalities are minimal, despite the fact that the blockade obtained reaches thoracic levels. 4 Specifically in asthmatic patients, there appears to be a lower risk of bronchospasm under regional anaesthesia compared to general anaesthesia, the main goal being the elimination of neural reflexes caused by intubation which have been found to give rise to the contraction of the smooth muscles of the tracheobronquial tree. However, bronchospasm following spinal anaesthesia is extremely rare in healthy patients as well as in patients with bronchial disease.…”
Section: Discussionmentioning
confidence: 99%